2016
DOI: 10.1159/000450865
|View full text |Cite
|
Sign up to set email alerts
|

Out-Patient Management of Mild or Uncomplicated Diverticulitis: A Systematic Review

Abstract: Background: Management of diverticular disease has undergone a paradigm shift, with movement towards a less invasive management strategy. In keeping with this, outpatient management of uncomplicated diverticulitis (UD) has been advocated in several studies, but concerns still remain regarding the safety of this practice. Aim: To assess outcomes of out-patient management of acute UD. Methods: A comprehensive search for published studies using the search terms ‘uncomplicated diverticulitis', ‘mild diverticulitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
2
17
0
5
Order By: Relevance
“…Ambulatory treatment was associated with daily cost savings of between 600 and 1,900 EUR per patient treated. One study showed that provision of care by an integrated multidisciplinary digestive health service can significantly reduce overall costs (p = 0.0497) and the length of hospital stay (p = 0.017) in patients admitted for diverticulitis compared to costs for care provided by nonintegrated inpatients services [63]. Moreover, a recent systematic review showed that care by gastroenterologists was associated with a significantly shorter length of stay than care provided by general physicians [64].…”
Section: Burden Of Diverticular Diseasementioning
confidence: 99%
“…Ambulatory treatment was associated with daily cost savings of between 600 and 1,900 EUR per patient treated. One study showed that provision of care by an integrated multidisciplinary digestive health service can significantly reduce overall costs (p = 0.0497) and the length of hospital stay (p = 0.017) in patients admitted for diverticulitis compared to costs for care provided by nonintegrated inpatients services [63]. Moreover, a recent systematic review showed that care by gastroenterologists was associated with a significantly shorter length of stay than care provided by general physicians [64].…”
Section: Burden Of Diverticular Diseasementioning
confidence: 99%
“…In a review of 10 studies comparing inpatient and outpatient management, similar failure rates (6.5% versus 4.6%) and recurrence rates (13.0% versus 12.1%) were found, and in a meta‐analysis of 2303 patients, there was only a 7% readmission rate, 0.4% need for emergency intervention and a 40–80% reduction in overall cost with outpatient treatment . Whilst the data are largely comprised of retrospective reviews and randomized trials with notable limitations, the safety of outpatient management of uncomplicated diverticulitis in well‐selected patient groups remains quite convincing.…”
mentioning
confidence: 79%
“…In addition, in terms of follow‐up, the rate of patients seen subsequently in our outpatient service decreased from 53% to 22%. This, along with the significant decrease in hospital admissions should translate to significant reductions in healthcare costs with a decreased burden on hospital resources …”
Section: Discussionmentioning
confidence: 99%